2014
DOI: 10.1007/s12105-014-0559-z
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Claudin-1 is Associated with Advanced Clinical Stage and Invasive Pathologic Characteristics of Oral Squamous Cell Carcinoma

Abstract: Claudins constitute a group of principal proteins forming the tight junctional complex. The altered expression of selected claudins has been reported in several human cancers. The purpose of this study was to investigate the expression of claudin-1 and claudin-4 in oral squamous cell carcinoma (OSCC) and examine its relationship with patient clinical-pathologic features. Fortyfive OSCC cases were enrolled. Patient clinical, pathologic and follow-up data were reviewed and the claudin-1 and claudin-4 expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
3
33
1
Order By: Relevance
“…High expression of CLDN-1 in our study was associated with the histological grades which allowed us to assume that CLDN-1 might be involved in the progression of cancer either directly or indirectly. Similar results were observed by Sappayatosok et al 37 , who reported an association of CLDN-1 overexpression with the advanced clinical stage. Also, deregulation and delocalization of CLDN-1 from the cell membrane to the cytoplasm to the nucleus during the progression of oral cancer confirms its unidentified role in cell signaling.…”
Section: Discussionsupporting
confidence: 90%
“…High expression of CLDN-1 in our study was associated with the histological grades which allowed us to assume that CLDN-1 might be involved in the progression of cancer either directly or indirectly. Similar results were observed by Sappayatosok et al 37 , who reported an association of CLDN-1 overexpression with the advanced clinical stage. Also, deregulation and delocalization of CLDN-1 from the cell membrane to the cytoplasm to the nucleus during the progression of oral cancer confirms its unidentified role in cell signaling.…”
Section: Discussionsupporting
confidence: 90%
“…The areas in one study (total 99 patients) included the tongue (44%), floor of mouth (24%), floor of mouth and tongue (13%), alveoli (13%), buccal mucosa (5%), and retromolar trigone (1%) . Those of the other study (total 45 patients) included the gingiva (38%), tongue (16%), floor of mouth (18%), buccal mucosa (13%), hard palate (7%), and alveolar mucosa (9%) . In the present study, we focused on TSCC, which may explain the different conclusions obtained between the previous and present studies.…”
Section: Discussionmentioning
confidence: 49%
“…Previously, claudin‐1 overexpression was reported to be associated with invasive pathological characteristics in OSCC in two independent studies which analyzed various regions in the oral cavity . The areas in one study (total 99 patients) included the tongue (44%), floor of mouth (24%), floor of mouth and tongue (13%), alveoli (13%), buccal mucosa (5%), and retromolar trigone (1%) .…”
Section: Discussionmentioning
confidence: 99%
“…The authors of the study further revealed elevated expression of CLDN-1 in OSC-4 and NOS-2 cell lines which are highly invasive [129]. One study demonstrated the association of high CLDN-1 expression with aggressive histopathologic features such as perineural and vascular invasion and suggested that CLDN-1 might be directly or indirectly involved in the progression of OSCC [130]. Another study found that the absence of CLDN-1 was associated with poorly differentiated tumors [131].…”
Section: Claudin-1 and Oral Squamous Cell Carcinomamentioning
confidence: 94%